Rip Current Hazard in Klayar Beach, Pacitan, Indonesia: Inferred from Fluorescent Dye and UAV - Wahyudi, Wahyudi; Fatchurohman, Hendy; Natasya, Verent Priscillia Rahayu; Sujantoko, Sujantoko; Sembiring, Leo Eliasta (International Journal of Marine Engineering Innovation and Research, 2024)
South coasts of Java have a unique landscape that exhibits exotic and phantastic natural view which is very attractive as tourist destinations. Indonesia has the world’s longest coastlines, the world’s highest coral diversity, and spectacular seascapes, therefore Indonesia’s coastal tourism potential is very promising. However, despite their attractiveness coastal water can be very dangerous to their visitors due to rip currents which isinhospitable to them. Klayar Beach (KB) is one of the most popular recreational beaches in Pacitan Regency, East Java Province, Indonesia. However, KB poses a hazard due to rip currents. This paper presents the result of field observations of rip currents utilizing fluorescent dying and unmanned aerial vehicle (UAV).  We used UAV multirotor DJI Mavic 2 Zoom with video camera to take and monitor aerial photo and video of rip current flows. The result of this study proves that there is rip currents in KB. It also reveals that the maximum velocity reaches 0.8 m/s, with average width of 11 m, and total length 99.99 m. The type of rip current in the KB is structural boundary controlled and predicted as a permanent rip. Therefore, this evidence should be considered for promoting beach safety in this area.